Masjid: Bentuk Manifestasi Seni dan Kebudayaan - Aulia Fikriarini Muchlis (el Harakah: Jurnal Budaya Islam, 2009)
Cultural  value can determine the characteristics of cultural environment in which those values believed. Hence, it is colored by the act of the society and the product of the culture. In this sense, human  beings as the main actor of that existing culture. One of the visible products of the culture is its art (architecture) as the proof that best  describes the situation  of the culture. The architecture also influences the ups and downs of a civilization, and it is more meaningful creating the combination between human culture and the human’s obedience to the God which shows harmonious relationship among human, environment, and the creator. It, then, will emerge as an Islamic new civilization, and will bring the goodness for human  beings. This paper describes a mosque as not only the symbol of syi’ar Islam for praying and i’tikaf,  but something that has wider role. It is the creation of Islamic cultural value.  It means that the mosque was born from the knowledge that is inspired from spiritual values, therefore, it reminds and guides human  to come back to the God. Nilai budaya dapat menentukan karakteristik lingkungan budaya di mana nilai-nilai itu dipercaya. Oleh karena itu, nilai budaya diwarnai oleh tindakan masyarakat dan produk budaya. Dalam pengertian ini, manusia sebagai aktor utama dari budaya yang ada. Salah satu produk budaya adalah seni (arsitektur) sebagai bukti yang paling menggambarkan situasi budaya. Arsitektur juga mempengaruhi naik turunnya peradaban, dan ini lebih berarti menciptakan kombinasi antara budaya manusia dan ketaatan manusia terhadap Tuhan yang menunjukkan hubungan yang harmonis antara manusia, lingkungan, dan sang pencipta. Ini kemudian akan muncul sebagai peradaban baru Islam, dan akan membawa kebaikan bagi manusia. Makalah ini menjelaskan bahwa masjid tidak hanya sebagai simbol syi'ar Islam untuk shalat dan i'tikaf, tapi sesuatu yang memiliki peran lebih luas. Inilah ciptaan budaya Islam nilai. Artinya masjid itu lahir dari pengetahuan yang ada Terinspirasi dari nilai spiritual, oleh karena itu, ini mengingatkan dan membimbing manusia untuk kembali kepada Tuhan